OGM e ostie a basso contenuto di glutine. La comunione dei fedeli celiaci: una questione ancora aperta (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Le norme sulla Santa comunione dei fedeli celiaci - 2. Le recenti linee guida emanate su richiesta di Papa Francesco - 3. Il pane mere triticeus come insostituibile elemento dell’Eucarestia - 4. La fonte della liturgia cattolica sul divieto dell’uso di ostie gluten free come materia eucaristica: il pane dell’ultima cena - 5. Il glutine come parte del pane eucaristico - 6. Il fedele celiaco e la Santa comunione tra ostie a basso contenuto di glutine, comunione sub sola specie vini e comunione spirituale - 7. L’uso di organismi geneticamente modificati (OGM) nell’Eucarestia e la genuinità della materia eucaristica - 8. Conclusioni.GMO and low gluten host. The communion of the celiacs faithful: an open questionABSTRACT: Celiac disease is an autoimmune disorder triggered by gluten in susceptible individuals. Currently, there is no specific medical treatment for celiac disease. The only treatment for this disorder is lifelong adherence to a gluten-free diet. Catholic Church affirmed that bread, to be valid material for the Eucharist, must be made of wheat, must contain enough gluten for breadmaking and must be free of foreign matter. In order to meet the needs of those who suffer from the celiac disease, it has introduced the validity of low gluten. The Circular Letter issued at the request of Pope Francis has not changed the Holy Communion of the celiac faithful. Nevertheless, the document also decided that Eucharistic matter made with OGM could be considered valid matter. The Roman rite finds its theological source in the elements of Eucarist by Jesus instituted in the Last Easter Supper. The sources, however, do not indicate the matter of the bread offered at the Last Supper. So can we say that it was really made of wheat? The solution to this enigma is very important. In fact, it could open up new horizons on Eucharistic matter and on the validity of the gluten free hosts.